Volumetric Bone Mineral Density in Cementless Total Hip Arthroplasty in Postmenopausal Women: Effects on Primary Femoral Stem Stability and Clinical Recovery - Aro, Hannu T.; Engelke, Klaus; Mattila, Kimmo; Löyttyniemi, Eliisa (Journal of Bone and Joint Surgery-American Volume, 2021)
BACKGROUND: In cementless total hip arthroplasty, femoral stems should preferably not migrate at all postoperatively. This goal is difficult to achieve in postmenopausal women with impaired bone quality. Here, we explored the clinical importance of initial stem migration, measured by radiostereometric analysis (RSA), in women who underwent quantitative computed tomography (CT) of the involved hip preoperatively. METHODS: A prospective cohort of 65 postmenopausal women (mean age, 69 years) with hip osteoarthritis and Dorr type-A or B femoral anatomy underwent total hip arthroplasty with implantation of a tapered, single-wedge femoral stem. Volumetric bone mineral density (BMD) was measured using quantitative CT. Femoral stem translation and rotation were measured using model-based RSA within 3 days after the surgical procedure and were repeated at 3, 5, and 11 months. Postoperative recovery parameters included walking speed, walking activity, and patient-reported outcome measures. Subjects were categorized into 2 groups according to the magnitude of initial 5-month stem subsidence (<2 mm or ≥2 mm); RSA outliers (n = 7) were analyzed separately. RESULTS: Subjects with stem subsidence of ≥2 mm (mean, 3.09 mm [95% confidence interval (CI), 2.70 to 3.47 mm]) had lower intertrochanteric volumetric BMD (p = 0.008). Subjects with subsidence of <2 mm (mean, 0.80 mm [95% CI, 0.51 to 1.09 mm]) had faster improvement of patient-reported outcome measures and exhibited faster walking speed (p = 0.007) and greater walking activity (p = 0.010) at 11 months as well as better Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) scores (p = 0.002) and RAND 36-Item Health Survey mental component scores (p = 0.006) at 2 years. All cohort stems were osseointegrated at 2 years. CONCLUSIONS: Femoral stem stability and resistance to subsidence were sensitive to adequate intertrochanteric volumetric BMD. Low intertrochanteric volumetric BMD was associated with greater stem migration. With initial migration, clinical recovery was slower and patient-reported outcome measures were less satisfactory. LEVEL OF EVIDENCE: Prognostic Level II. See Instructions for Authors for a complete description of levels of evidence.
CRIS-Team Scopus Importer:2021-06-25